How effective is our telephone triage service at providing specialist palliative care?. Issue 2 (1st September 2011) - Stananought, Nicola; Sutherland, Jane
Abstract : Introduction: In 2006, we enhanced our specialist telephone triage service to keep pace with the increasing demands of providing accessible specialist palliative care to all with life limiting illness. Early statistical analysis revealed that the service was invaluable in coping with increased demand but were telephone triage patients receiving an effective service? In August 2010, a retrospective caseload analysis was undertaken to establish this point. Aims: To determine the ability of the telephone triage service to reduce patient STAS (Support Team Assessment Schedule, Higginson 1993) scores or to refer on appropriately. To compare results with the community team's ability to reduce patient STAS scores. To highlight trends in types of care provided for patients managed by the telephone triage service. Methods: The telephone triage service uses an adapted version of the Support Team Assessment Schedule tool to assess patients. 50 randomly chosen patients were recruited, with at least one problem scoring STAS 3 or above at triage first contact telephone assessment. Analysis of STAS scores was undertaken at subsequent contacts, along with referral patterns and time lapses between contacts. Results: At the second telephone triage contact, the number of problems scoring STAS 3 or above had reduced by 60%. A third telephone contact reduced the number scoring STAS 3 or above even further. Outcome scores for the community team were very similar. Conclusion: The very nature of palliative care means that as initial STAS scores are reduced, new and often more complex problems develop. However, results clearly demonstrate that our telephone triage service is effective in palliating symptoms. Introducing telephone triage into our service has successfully reduced our waiting lists by providing a flexible, responsive service appropriate to need. We are now able to confidently evidence the effectiveness of this service in terms of providing high quality specialist palliative care.